The Multilayered Prehistory of Wild Aurochs and Domestic Cattle - (:unkn) unknown (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2018)
This thesis explores 122 ancient genomes of domestic cattle and wild aurochs to investigate past population events such as domestication and admixture. Population genomics of ancient taurine domestics from the ancient Near East and Europe support a centre of domestication in the Near East for Bos taurus. Subsequent dispersal of domestic cattle into Europe was followed by gene flow from European wild aurochs for thousands of years. Genome-wide data of 18 Bos primigenius samples from Asia, North Africa and Europe reveals new mtDNA and Y chromosome haplogroups, as well as support for gene flow with ancient domestics. Admixture between Bos taurus and Bos indicus in the Near East was confirmed by analysing 67 ancient domestic individuals across Western Asia, in a temporal context of 8000 years. Zebu cattle were likely introduced in the Near East first during the Bronze Age, with the expansion of Mesopotamian and Harappan civilizations, with gene flow occurring for thousands of years. It was also demonstrated the potential for low coverage aDNA data to infer on past population history and to fill in gaps in the genetic prehistory of wild and domestic cattle.
An Ancient Genomics Perspective
APPROVED
Keywords: aurochs; domestication; cattle; ancient DNA; population genetics; genomics; Zebu; Bos taurus; Bos indicus; genetics; Bos primigenius; Near East; taurine